Connecting the public with clinical trial options: The ResearchMatch Trials Today tool. Issue 4 (27th November 2018) - Pulley, Jill M.; Jerome, Rebecca N.; Bernard, Gordon R.; Olson, Erik J.; Tan, Jason; Wilkins, Consuelo H.; Harris, Paul A.
Abstract : Potential participants seek information about clinical trials for many reasons, but the process can be challenging. We analyzed 101, 249 searches in ResearchMatch Trials Today, a free interface to recruiting trials from ClinicalTrials.gov. Searches from March 2015 to November 2016 included a broad range of conditions and healthy volunteer concepts, including 12, 649 unique topics. Trials Today data indicate that it is being used to identify trials on a variety of topics.